POSITIVE PSYCHOLOGICAL INTERVENTION IN IMPROVING SELF-CONFIDENCE OF BREAST CANCER SURVIVORS IN MOTHERS WHO DO NOT WORK - Junizar; Rika Dewi; Afni Yan Syah; Neiliel Fitriana Anies; Dewiyuliana (CV. RADJA PUBLIKA, 2024)
In Indonesia, cases of breast cancer continue to increase, various methods are used to obtain a cure and prevent the spread of cancer cells, including mastectomy, chemotherapy and radiotherapy. The treatment will have an effect on physical, psychological and social changes. The physical appearance of breast cancer patients changes from before and after therapy, with these changes it will have an impact on psychological changes, namely a lack of self-confidence so that breast cancer patients tend to withdraw from their family and friends. The purpose of this study was to see the impact of positive psychology interventions in increasing the self-confidence of breast cancer survivors in mothers who do not work. This study is a quantitative study. The data collection tool in this study uses a self-confidence scale. This study uses QuasyExperimentwith the pretest and posttest design approach. Sample selection using purposive sampling method totaling 25 respondents, the researcher conducted a Paired Sample T Test Statistical test with a reference value of p-value <0.05. The results of this study are with a p-value of 0.000. So it can be concluded that positive psychology intervention can increase the self-confidence of breast cancer survivors in unemployed mothers.